PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI RA HABIBIE SINGOSARI KABUPATEN MALANG - Ade Lissa Pepita Koes Hera Sari; Anwar Sa’dullah; Eko Setiawan (UNISMA, 2021)
Education as an important means to prepare students to develop a variety of values and skills that are applied from an early age to adulthood. Education is used as a reference in society, nation and state. The importance of education for each individual is emphasized in Law Number 20 of 2003 about the National Education System. The professionalism of teachers at RA Habibie is still low. This can be seen in the ability of teachers when teaching using the monotonous method and some teachers have not met the qualifications of S-1. This study aims to determine the role of school principals in improving teacher professionalism and the obstacles that exist in RA Habibie. Researchers determine the focus of research on teacher professionalism, the role of school principals in improving teacher professionalism, and principal obstacles in improving teacher professionalism. The researcher uses a qualitative approach with the type of case study research. The researcher acts as a key instrument, the data collection technique is done by triangulation. The results of this study are that in teaching and learning activities, teacher preparation in teaching must be ready, the teacher understands the material to be delivered; the principal's role as educator, supervisor, manager, administrator, leader, innovator, motivator has been implemented but needs to be improved again; and the obstacles are low support for school programs from all parties, weak teacher competence, inadequate budget and infrastructure for educational success.